Thoracic Outlet Syndrome - Illig, Karl A.; Thompson, Robert W.; Freischlag, Julie Ann.; Donahue, Dean M.; Jordan, Sheldon E.; Edgelow, Peter I.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Thoracic outlet syndrome (TOS) is a condition estimated to affect as many as 80 of every 1000 patients in the US alone. While estimates vary widely based in part on lack of consensus as to the definition of the syndrome, as many as 3000 first rib resections are performed annually in the US. TOS comprises at least three separate conditions. The most common, neurogenic TOS, refers to the condition where the brachial plexus is compressed at the scalene triangle or retropectoral space, and is manifest as local and extremity pain and neurologic symptoms. Venous TOS refers to the situation where the subclavian vein is compressed by the structures making up the costoclavicular junction, and presents as acute or chronic venous thrombosis or injury or occasionally intermittent positional obstruction. Finally, arterial TOS refers to the situation where arterial injury occurs as the result of abnormal bony or ligamentous structures at the outlet, and presents as occlusion of or embolization from an abnormal artery in this area. Thoracic Outlet Syndrome brings together many experts who treat this disease and are leaders in their fields. While it can certainly be read in its entirety (and should, by all who concentrate on this condition), it is designed to be a clinical reference, residing on a shelf in a busy surgical, vascular or neurologic clinic where individual chapters can be quickly referenced. As such, the chapters are thorough, but concise and useful to answer when a specific question arises in the course of daily practice.
Part I Background and Basic Principles -- Part II Neurogenic TOS: General Principles -- Part III Neurogenic TOS: Surgical Techniques -- Part IV Neurogenic TOS: Outcomes and Future Directions -- Part V Neurogenic TOS: Controversies in NTOS -- Part VI Venous TOS: General Principles -- Part VII Neurogenic TOS: Surgical Techniques -- Part VIII Neurogenic TOS: Outcomes and Future Directions -- Part IX Neurogenic TOS: Controversies in VTOS -- Part X Arterial TOS: General Principles -- Part XI Neurogenic TOS: Surgical Techniques -- Part XII Neurogenic TOS: Outcomes and Future Directions -- Part XIII Additional Topics Related to Thoracic Outlet Syndrome.
Keywords: Medicine; Cardiology; Neurology; Neurosurgery; Psychiatry; Thoracic surgery; Medicine & Public Health; Cardiology; Neurology; Thoracic Surgery; Neurosurgery; Psychiatry